Observation of the effect of artificial dermis technology combined with full-thickness skin graft coverage in the treatment of foot and ankle wound defects in the elderly - Qiang Xie; Yu Hao; Yu Kong; Pei Wang (Journal of Orthopaedic Surgery)
Purpose To analyze the effect of artificial dermis technology combined with full-thickness skin graft coverage in the treatment of foot and ankle wound defects in the elderly. Methods A total of 90 elderly patients treated for foot and ankle wound defects from January 2021 to December 2022 were selected as the study subjects and were divided into a control group of 40 cases and a study group of 50 cases according to the random number table method. The control group was treated with retrograde saphenous nerve flap transplantation, while the study group was treated with artificial dermis technology combined with full-thickness skin graft coverage. The therapeutic effect of artificial dermis technology combined with full-thickness skin graft coverage was observed. The ankle function, pain level, postoperative wound recovery, relevant indicators, and postoperative wound complications were compared between the two groups. Results At 2 and 4 weeks after treatment, the ankle function of both groups was higher than before treatment, and the ankle function of the study group was higher than that of the control group ( p < .05). At 2 and 4 weeks after treatment, the VAS and PPI scores of both groups were lower than before treatment, and the VAS and PPI scores of the study group were lower than those of the control group ( p < .05). Compared with the control group, the study group had lower color, thickness, vascular distribution, and softness, as well as shorter surgical preparation time, hospital stay, antibiotic use, and fewer dressing changes. The overall incidence of flap edema, wound infection, and total wound infection was lower in the study group ( p < .05). Conclusion The use of artificial dermis technology combined with full-thickness skin graft coverage in the treatment of foot and ankle wound defects in the elderly helps to improve ankle joint function, reduce the degree of pain, and results in better postoperative wound recovery and a lower complication rate.